2015
DOI: 10.1364/oe.23.019846
|View full text |Cite
|
Sign up to set email alerts
|

Bifractal focusing and imaging properties of Thue–Morse Zone Plates

Abstract: Abstract:We present a new family of Zone Plates (ZPs) designed using the Thue-Morse sequence. The focusing and imaging properties of these aperiodic diffractive lenses coined Thue-Morse Zone Plates (TMZPs) are examined. It is demonstrated that TMZPs produce a pair of self-similar and equally intense foci along the optical axis. As a consequence of this property, under broadband illumination, a TMZP produces two foci with an extended depth of focus and a strong reduction of the chromatic aberration compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 23 publications
0
45
0
Order By: Relevance
“…In this way, like FiVLs, TMVLs are bifocals, but they produce a sequence of secondary foci around each main focus that have a fractal structure. In fact, it has been shown that irradiance provided by these lenses with topological charge m ¼ 0i s self-similar [51], that is, the irradiance distribution corresponding to a TMVL of order S is a modulated version of the irradiance distribution corresponding to the previous stage, S−1, magnified by a factor 2.…”
Section: Thue-morse Vortex Lensmentioning
confidence: 99%
See 2 more Smart Citations
“…In this way, like FiVLs, TMVLs are bifocals, but they produce a sequence of secondary foci around each main focus that have a fractal structure. In fact, it has been shown that irradiance provided by these lenses with topological charge m ¼ 0i s self-similar [51], that is, the irradiance distribution corresponding to a TMVL of order S is a modulated version of the irradiance distribution corresponding to the previous stage, S−1, magnified by a factor 2.…”
Section: Thue-morse Vortex Lensmentioning
confidence: 99%
“…On the other hand, in recent years different non-periodic and quasi-periodic sequences [22] have been also employed to design new types of ZPs with curious physical properties. Fractal zone plates (FrZPs) [23,24], Fibonacci zone plates (FiZPs) [25,26], Thue-Morse zone plates (TMZPs) [27] and some variations of these basic designs are representative examples [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibonacci zone plates are intrinsically bifocals, being the ratio of the two main focal distances defined by the golden ratio [11]. Thue-Morse zone plates combine the properties of fractal and Fibonacci zone plates producing two main self-similar foci along the optical axis with extended depth of focus [12].…”
Section: Introductionmentioning
confidence: 99%
“…These subsidiary foci of the FZP provide an extended depth of focus for each wavelength that partially overlaps with the other ones, creating an overall extended depth of focus that is less sensitive to chromatic aberration. However, the price paid to gain depth of field and reduce chromatic aberration is a reduced resolution, low energy efficiency, and strong background stray light 16 17 . In 2007, Andersen et al .…”
mentioning
confidence: 99%